Pengaruh Brand Awareness dan Perceived Value Terhadap Kepuasan Pelanggan Pengguna Simpati (Studi Kasus Pada Pengunjung PT. Koperasi Telkomsel Cabang Jombang) - Kholisa Tifany Ekaputri; Tri Sudarwanto (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
This study aims to determine the effect of brand awareness and perceived value oncustomer satisfaction of Simpati users. The method used in this research is quantitativeresearch methods. In this study data collection using a questionnaire and sampling asmany as 100 people who were visiting at PT. Telkomsel Cooperative Branch of Jombang.The results showed that: (1) Brand awareness has a partial effect on customersatisfaction of Simpati users, (2) Perceived value has a partial effect on customersatisfaction of Simpati users, (3) Brand awareness and perceived value have asimultaneous effect on customer satisfaction of Simpati users